Training courses in systematic reviews or in specific steps of systematic review for EFSA Risk Assessment. Issue 10 (17th October 2018) - de Vries, Rob; van Luijk, Judith; Hooijmans, Carlijn; Wever, Kim; Hoffmann, Sebastian; Hout, Joanna in t; Langendam, Miranda; Tillema, Alice; Alkema, Wynand; Ritskes‐Hoitinga, Merel; Leenaars, Marlies; ,
Abstract : The overall objective of project OC/EFSA/AMU/2015/04 was to support EFSA to develop in‐house capacity to perform systematic reviews in food and feed safety and extensive literature searches to inform systematic reviews. This objective had to be reached by offering 4 different types of training courses in (specific steps of) systematic reviews to EFSA staff (including Trainees) and Experts (of Panels, Working Groups and Member States). This report summarizes these trainings and their evaluation. Between 17 October 2016 and 11 April 2018, 22 trainings were delivered by a team of trainers from SYRCLE (SYstematic Review Centre for Laboratory animal Experimentation, www.syrcle.nl ) and partners. A total number of 339 people participated in these trainings (an average of 15 per training), some of whom participated in more than one training (day). The individual trainings were evaluated using an online evaluation form, which consisted of general questions (e.g. about the training room or course material) and specific questions about the various parts of the training courses. Moreover, the participants had the option of adding qualitative comments. With an average score of 8.53 out of 10, the trainings were evaluated very positively. Major revisions were only necessary for two of the four course types and only after the first editions. After that, the improvements suggested were only minor. Remarks such as This training was one of the most useful trainings I attended in the last couple of years were not uncommon. Based on the experiences with this series of trainings, recommendations are made for future EFSA trainings in evidence synthesis.© European Food Safety Authority, 2018